Poligami Bagi Aparatur Sipil Negara Berdasarkan Undang-Undang Nomor 1 Tahun 1974 Tentang Perkawinan - Saragih, Rahmayani (DE LEGA LATA: JURNAL ILMU HUKUM, 2018)
Law Number 1 of 1974 concerning Marriage, provisions concerning marriage have been regulated which apply to all Indonesian citizens, including those who are citizens of the status of civil servants. Civil servants must set a good example to their subordinates and set an example as good citizens in the community, also in organizing family life. In Law No. 1 of 1974 stated "Marriage is an inner and outer bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family / household based on the One Godhead, and recorded according to the applicable legislation". Surely eternal marriage is the dream of all families. In principle, in a marriage a man may only have a wife and a wife may only have a husband, but it does not rule out the possibility that a husband has more than one wife (polygamy) at the same time with certain conditions, this also applies to a male civil servant after certain conditions are met.